Avaliação da qualidade de projetos de software destinados ao setor de manufatura durante as etapas de desenvolvimento: uma contribuição - Lenhart, Diane (2024)
The variables involved in the software development process have an increasing level of complexity, causing the risks of malfunctioning of products derived from this process to increase considerably. Therefore, it is vital to evaluate the quality of software projects in the development stages. There are standards that help software developers to evaluate the quality of the product during these stages. However, there is a difficulty in using these standards due to their complexity of use, in addition to also requiring adaptation within the application context. Other problems surrounding the subject refer to the variables involved in evaluating the quality of software development, such as the functional size of the functionality delivered by a system and the programming language, which can interfere with the final quality. Within the context described, the objective of this work was to develop a structure to evaluate the quality of software products intended for the manufacturing sector during the development stages, to evaluate software products intended for the sector and to identify whether there is a difference in the final quality between products of different programming languages and functional sizes. To create the evaluation framework, concepts from the PMBOK® Guide (Project Management Body of Knowledge) and data containing metrics from software projects from different countries from the repository provided by the ISBSG (International Software Benchmarking Standards Groups) were used. To conclude the study objective, the AHP, ELECTRE TRI and ELECTRE III methods were used, using metrics from 539 projects from different countries. Through the results, it was concluded that software projects in the manufacturing sector are being carried out in an average way in their development, there is no significant difference in the functional size of the software and the languages PL/l, Visual Basic, C++ and Oracle had the best values, that is, projects with better quality during the development stages. It is expected that the results can contribute to the improvement of software quality in the manufacturing sector.